Calcium Apatite Deposition Disease: Diagnosis and Treatment - Nicholas M. Beckmann (Radiology Research and Practice)
Calcium apatite deposition disease (CADD) is a common entity characterized by deposition of calcium apatite crystals within and around connective tissues, usually in a periarticular location. CADD most frequently involves the rotator cuff. However, it can theoretically occur in almost any location in the musculoskeletal system, and many different locations of CADD have been described. When CADD presents in an unexpected location it can pose a diagnostic challenge, particularly when associated with pain or swelling, and can be confused with other pathologic processes, such as infection or malignancy. However, CADD has typical imaging characteristics that usually allows for a correct diagnosis to be made without additional imaging or laboratory workup, even when presenting in unusual locations. This is a review of the common and uncommon presentations of CADD in the appendicular and axial skeleton as well as an updated review of pathophysiology of CADD and current treatments.